TNFalpha-stimulated gene product (TSG-6) and its binding protein, IalphaI, in the human intervertebral disc: new molecules for the disc. - Roberts, S; Evans, H; Menage, J; Urban, J; Bayliss, M; Eisenstein, S; Rugg, MS; Milner, C; Griffin, S; Day, A (2005)
Inflammation and irritation of the nerve roots has been indicated as an important factor in the pain associated with symptomatic disc herniations. Tumour necrosis factor alpha (TNFalpha) is now believed to be involved in this pathway. TNFalpha causes connective tissue cells in culture to synthesise a glycoprotein, TNFalpha-stimulated gene-6 (TSG-6). TSG-6 is found in inflammatory diseases of related connective tissues, such as articular cartilage in rheumatoid arthritis, but is not present in unaffected individuals. In order to determine if TSG-6 occurred in intervertebral disc (and cartilage endplate), we have investigated the presence of TSG-6 and its binding protein, inter-alpha-inhibitor (IalphaI), in 58 herniated and 15 non-herniated discs. Immunostaining for the cytokines, IL-1alpha, IL-1beta and TNFalpha, has also been carried out. We have demonstrated that both TSG-6 and IalphaI occur commonly in human intervertebral disc matrix with at least some TSG-6 in 98% of discs studied and IalphaI in all of them. Staining for TSG-6 was greatest in herniated discs, particularly close to blood vessels. IalphaI immunostaining was frequently widespread throughout the disc but there was little in the cartilage endplate. It has been proposed that these molecules have widespread effects, including extracellular matrix stabilisation, down-regulation of the protease network and reduction of inflammation. Hence, the occurrence of TSG-6 and IalphaI in disc tissue could have implications in the aetiopathogenesis and future therapeutics of intervertebral disc disease.